A study on the morbid histopathological changes in COVID‐19 patients with or without comorbidities using minimally invasive tissue sampling. Issue 1 (21st December 2022) - Goel, Ayush; Ray, Animesh; Chavan, Amitkumar; Sahni, Shubham; Gupta, Baidhnath K.; Raut, Shrawan K.; Agarwal, Shubham; Nehra, Jagbir; Somu, Bharadhan; Raja, Ragu; Aakansha; Nagpal, Chitrakshi; et al.
Abstract: COVID‐19 causes morbid pathological changes in different organs including lungs, kidneys, liver, and so on, especially in those who succumb. Though clinical outcomes in those with comorbidities are known to be different from those without—not much is known about the differences at the histopathological level. To compare the morbid histopathological changes in COVID‐19 patients between those who were immunocompromised (Gr 1), had a malignancy (Gr 2), or had cardiometabolic conditions (hypertension, diabetes, or coronary artery disease) (Gr 3), postmortem tissue sampling (minimally invasive tissue sampling [MITS]) was done from the lungs, kidney, heart, and liver using a biopsy gun within 2 hours of death. Routine (hematoxylin and eosin) and special staining (acid fast bacilli, silver methanamine, periodic acid schiff) was done besides immunohistochemistry. A total of 100 patients underwent MITS and data of 92 patients were included (immunocompromised: 27, malignancy: 18, cardiometabolic conditions: 71). In lung histopathology, capillary congestion was more in those with malignancy, while others like diffuse alveolar damage, microthrombi, pneumocyte hyperplasia, and so on, were equally distributed. In liver histopathology, architectural distortion was significantly different in immunocompromised; while steatosis, portal inflammation, Kupffer cell hypertrophy, and confluent necrosis were equally distributed. There was a trend towards higher acute tubular injury in those with cardiometabolic conditions as compared to the other groups. No significant histopathological difference in the heart was discerned. Certain histopathological features were markedly different in different groups (Gr 1, 2, and 3) of COVID‐19 patients with fatal outcomes.